Knowledge Audit (A Brief Review on Concepts and Methodologies) - Shoa Hasani, Ahmadreza; Taghvaei, Abolghasem; Shayan, Ali (Global Science Independent Journal, 2020)
In the late 21st century, knowledge became the most meaningful resource of globalized economy. It is the knowledge that determines the health of all business in high tech manufacturing, services or information sectors. Knowledge management is the solution to the issue. As Peter Drucker declared: We cannot manage what we do not know how to measure! So the knowledge audit, the first step of knowledge management implementation in organizations, as a key success factor is the best answer to understand how and what we could measure! This literature defines different aspects of knowledge audit as the solution for organizations’ knowledge needs.